Students’ anxieties towards learning using moodle - Guruh Kemilo Rahari; Lusiana Vernanda; Friska Putri Oktavianti; Fitri Nur Hidayati; Fitri nurdianingsih; Ima Isnaini Taufiqur Rohmah; Dila Charisma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
Anxiety is an unpleasant condition, emotional in nature and very strong, accompanied by a physical sensation that warns a person of approaching danger. This unpleasant feeling is usually vague and difficult, sure but always felt. This study aimed to find out the factors that affect students’ anxieties towards learning using moodle. The interview was used to gain the data. The results show that: the factors that caused students anxieties in learning using moodle were: (1) students limited internet connection 43%; (2) students’ house location 21% ; (3) students’ limited understanding how to use moodle 12% ; (4) unidentified factors 26%. The current study suggested that further research to solve the students’ anxieties towards leraning using moodle was need to be conducted to complete the finding